Evaluation of the Effectiveness of the Standard Bidding Document for Design-Build Contracts in Road and Bridge Projects in Iraq (Journal of Engineering, 2025)
The implementation of Design-Build contracts within Iraq's Standard Bidding Document (SBD) framework is essential for the enhancement of road and bridge infrastructure. This study assesses the effectiveness of the SBD for Design-Build contracts in reducing cost overruns and schedule delays using a mixed-methods approach that includes a questionnaire survey of 65 professionals, case study analysis of five completed projects, and expert interviews.  Survey data revealed agreement on the SBD's efficacy in improving procurement transparency and cost control; however, its ability to address design modifications gained less approval. Case studies validated these findings, indicating that projects with major design changes encountered significant schedule growth, although cost parameters remained consistent in all instances. Interviews identified unforeseen infrastructure conflicts and iterative design adjustments as critical delay factors, highlighting gaps in the SBD's adaptability provisions.  The study concludes that while the SBD provides robust financial governance, its rigid structure impedes responsive design management. Future revisions to Iraq's SBD framework must prioritize the integration of dynamic adaptability frameworks, improve risk allocation, and incorporate design-review methods to systematically mitigate emergent complexities and optimize infrastructure delivery outcomes. The findings provide practical insights for infrastructure policy in Iraq, particularly for the Ministry of Planning, responsible for organizing and updating the SBDs, as well as for implementing agencies such as the Ministry of Construction, Housing and Public Municipalities, Roads and Bridges Directorate, and Mayoralty of Baghdad. These findings support reviewing key provisions to ensure effective management of design changes, reduce delays, and enhance project implementation efficiency.